Deconstructing Gender Bias in Child Custody Decisions in the Indonesian Legal System - Adriel, Kenneth; Hadiati , Mia (Jurnal Ilmu Hukum Kyadiren, 2025)
This study is motivated by the growing complexity of post-divorce child custody determinations, particularly in cases where the mother declines her custodial responsibilities and the father petitions for custody as the primary caregiver. The objective of this research is to analyze the legal basis and judicial considerations underlying the assignment of custody rights to fathers, to identify the influence of social, psychological, and financial factors on such decisions, and to assess the contribution of these elements to strengthening the best interests of the child principle. Employing a normative legal approach, this study centers on the Cikarang District Court Decision No. 38/Pdt.G/2019/PN Ckr as its case study. The findings reveal that the court’s ruling was grounded in legal documentation, the child’s emotional condition, environmental stability, and the father's financial capability. The study concludes by underscoring the critical importance of prioritizing the child's best interests over gender-based assumptions and advocates for more responsive, evidence-based, and child-centered custody policies in Indonesia.